Effects of metal oxide catalysts on polycyclic aromatic hydrocarbons emissions from large scale biomass pyrolysis - Parviz Norouzmehr; Ahmad Reza Rabbani; Hamid Reza Zolfagharpour (Scientific Reports)
Abstract Biomass, as a renewable resource, offers a potential alternative to fossil fuels. Catalytic pyrolysis, a process that converts biomass into bio-oil, is a promising method for sustainable energy production. This study aimed to quantify the concentrations of 16 priority polycyclic aromatic hydrocarbons (PAHs) in bio-oil produced from metal oxide catalytic pyrolysis of sugarcane bagasse. Using a large-scale auger reactor, bagasse was pyrolyzed at temperatures ranging from 400 to 600 °C with various amounts of vanadium pentoxide (V2O5) catalyst (0–30% w/w). The resulting bio-oil was analyzed using gas chromatography/mass spectrometry (GC/MS) to identify and quantify PAHs. Significant levels of PAHs (2206–6498 mg/L) were detected in the bio-oil. Low molecular weight PAHs, such as naphthalene, acenaphthylene, acenaphthene, fluorene, and phenanthrene, were predominant in all samples. The minimum total PAHs concentration (2206 mg/L) was observed at 400 °C with a 20% V2O5 catalyst loading. These findings suggest that metal oxide catalytic pyrolysis of bagasse, particularly with V2O5, can effectively control and reduce the formation of PAHs. Further research is needed to optimize the process and minimize PAHs production to commercialize bio-oil as a sustainable fuel.